Synthesis and Evaluation of Mutual Azo Prodrugs of Sulfamethoxazole and Salicylic Acid Derivatives for Colon Targeted Release: Pharmaceutical Science-Public Health - Kumar, Anoop; Mishra, Ashutosh (International Journal of Life Science and Pharma Research, 2022)
Several adverse effects are related to medications that treat moderate to severe inflammatory bowel diseases (IBDs). Targeted drug administration is necessary to treat inflammatory bowel disease to maximize efficacy and minimize toxicity. This study investigated the prodrug approach for antibacterials that target the colon. We chose sulfonamide (Sulfamethoxazole) as an antibiotic to target the colon. The prodrug approach is one of the most effective treatments for inflammatory bowel disease (IBD), and this mutual azo prodrug might serve the same function. This investigation aims to synthesize mutual azo prodrugs (S1-S5) and evaluate the colon-targeted release (in-vitro and in-vivo release studies). The objective of synthesizing mutual azo prodrugs (S1- S5) is that due to the high molecular weight of synthesized prodrugs (>500), they will enter the colon intact and not be absorbed in the upper GIT (Lipinski rule of 5). A coupling reaction between the sulfamethoxazole diazonium salt and salicylic acid derivatives allowed for synthesizing of mutual azo prodrugs (S1-S5). By monitoring the chemical reactions, the purity of the synthesized prodrugs was assessed, and by using FTIR, NMR (1H and 13C), Mass Spectrometry (MS), and Elemental Analysis, the structures of newly synthesized mutual azo prodrugs (S1-S5) were analyzed. Studies on the in-vitro stability of synthesized prodrugs showed less release after 6 hours in HCl buffer (pH 1.2), and only 10% release after 6 hours in phosphate buffer (pH 7.4) was observed. The sensitivity of the synthesized azo prodrug to the bacterial enzyme azoreductase was shown by incubating the azo prodrugs with the cecal contents of a rat; the release results showed that the release of free drugs from the azo prodrugs was more than 80%. Using trinitrobenzene sulfonic acid (TNBS)-induced colitis rats model, the in-vivo study was evaluated, and results revealed that mutually synthesized azo prodrugs are effective as 5-aminosalicylic acid in ulcerative colitis. Based on the release studies results, it is concluded that the azo prodrugs are a potential therapeutic target for ulcerative colitis.